Los niveles carbonatados del Cámbrico Inferior de Alcolea (Córdoba,España) - Menéndez Carrasco, Silvia (Coloquios de Paleontología, 1999)
A palaeontological and sedimentologic study and analysis of the carbonate beds lroni the Lower Cambrian of Siena de Córdoba, near Alcolea (Córdoba). have allowed us to recognize the presence of calciniicrobial mounds witb several taxa of archaeocyaths. In ibis work we include the resulis obtained trom taxonomic, biostratigrapbic and palaeobiogeographic siudies related to these archaeocyaths, as well as the infonnation gasbered from dic stratigrapbic and sedimentologic analysis of dic rocks.
Keywords: Ossa Morena Zone Lower Canibrian; Lower Ovotian; Archaeocyaths Mounds; Sierra de Córdoba; Spain